Public office, private interests : accountability through income and asset disclosure : a companion volume to Income and asset disclosure : case study illustrations - World Bank; Stolen Asset Recovery Initiative (Washington,D.C World Bank, 2012)
The fight against corruption is a developmental imperative. While international efforts have achieved some significant results, they also illustrate the extent of the challenges that remain. A key lesson of experience is that tackling corruption needs to be waged simultaneously on two fronts: prevention and enforcement. Both approaches are complementary and self-reinforcing. The vast scale of illicit financial flows from the proceeds of corruption and the challenges associated with national and international asset recovery efforts call, in particular, for significant investments in prevention and a broadening of prevention tools. Income and asset disclosure (IAD) systems are gaining prominence as a tool in the fight against corruption, and have the potential to support efforts in both prevention and enforcement. This contribution is recognized in the United Nations Convention against Corruption (UNCAC) and other international anticorruption agreements. Chapter one of this guides provides an overview of the objectives of IAD systems, identifies the relevant international anticorruption instruments, and provides a summary of key considerations that should influence the design, implementation, and enforcement of an IAD framework. Chapters two and three drill down into the design of IAD systems and address practical aspects of implementation.
"A companion volume to: Income and asset disclosure : case study illustrations." "Stolen Asset Recovery Initiative."
Includes bibliographical references (p. 145-150).
Keywords: Corruption; POLITICAL CORRUPTION; ECONOMIC ASPECTS; ASSETS; TRANSPARENCY